Menggali Potensi TikTok: Pendekatan Pemasaran Digital Produk Kecantikan ‘FAV BEAUTY’ - Hadi Surya, Dalvin; Erdiansyah, Rezi (Prologia, 2024)
This research analyzes the role of the TikTok social media platform as a means of marketing communication for the "FAV BEAUTY" product through a qualitative approach with the characteristics of the Integrated Marketing Communication (IMC) theory. In this context, the research aims to explore how TikTok can be effectively integrated into marketing strategies to enhance brand communication and deepen consumer engagement. Qualitative research methods were employed, including in-depth interviews with consumers, content analysis of TikTok related to "FAV BEAUTY," and observations of the marketing campaigns run by the brand. The research findings indicate that TikTok can create more personal and emotional interactions between the brand and consumers by combining visual elements, music, and user creativity. Within the framework of the IMC theory, this research provides a comprehensive understanding of how TikTok can be integrated into a holistic marketing strategy, where marketing messages are coordinated effectively across various communication channels. The implications of these findings not only offer practical insights for "FAV BEAUTY" but also contribute to marketing literature and IMC theory, highlighting the potential of TikTok as a vital communication tool in the context of beauty product marketing. Penelitian ini menganalisis peran media sosial TikTok sebagai sarana komunikasi pemasaran produk "FAV BEAUTY" melalui pendekatan kualitatif dengan karakteristik teori Integrated Marketing Communication (IMC). Tujuan penelitian untuk menggali bagaimana TikTok dapat diintegrasikan secara efektif dalam strategi pemasaran untuk meningkatkan komunikasi merek dan memperdalam keterlibatan konsumen. Metode penelitian kualitatif digunakan, termasuk wawancara mendalam dengan konsumen, analisis konten TikTok terkait "FAV BEAUTY," dan observasi terhadap kampanye pemasaran yang dijalankan oleh merek tersebut. Temuan penelitian menunjukkan bahwa TikTok mampu menciptakan interaksi yang lebih personal dan emosional antara merek dan konsumen, dengan menggabungkan elemen visual, musik, dan kreativitas pengguna. Dalam kerangka teori IMC, penelitian ini memberikan pemahaman mendalam tentang bagaimana TikTok dapat diintegrasikan dalam strategi pemasaran yang holistik, di mana pesan pemasaran terkoordinasi secara efektif melalui berbagai saluran komunikasi. Implikasi temuan ini tidak hanya memberikan wawasan praktis bagi "FAV BEAUTY" tetapi juga menyumbang pada literatur pemasaran dan teori IMC, menyoroti potensi media sosial TikTok sebagai alat komunikasi yang penting dalam konteks pemasaran produk kecantikan.